Teachers’ Didactical Challenges in Implementing Technology Integrated Project-Based Learning in Mathematics - Ramadhani Ramadhani; Heri Retnawati; Syukrul Hamdi (MASI Mandiri Edukasi, 2026)
This study examines the didactic challenges experienced by mathematics teachers in implementing technology-integrated Project-Based Learning (PjBL) in North Sumatra, Indonesia. Previous studies have focused mainly on student outcomes, while limited attention has been given to teachers’ didactic work in managing projects, technology, and mathematical understanding simultaneously. This study aims to analyze how teachers interpret and negotiate these challenges so that technology supports mathematical reasoning rather than functioning only as instructional media. A qualitative phenomenological design was employed involving 22 high school mathematics teachers selected through purposive criterion sampling. Data were collected through open-ended interviews and analyzed using phenomenological thematic analysis assisted by NVivo. The findings identified six major themes: tensions between project activities and conceptual depth, technology as a didactic black box, classroom management complexity, challenges in statistical reasoning, assessment dilemmas, and reflective didactic work. Teachers used technologies such as GeoGebra, Canva, Excel, Google Classroom, and Quizizz, yet most served primarily as presentation tools rather than as cognitive tools for mathematical thinking. The study contributes to theory by proposing a pentagonal didactical structure comprising teacher, student, mathematics, technological artifact, and project.